Entangled Caribbean rewriting, C.L.R. James, Aimé Césaire, and their books as postcolonial lieux de mémoire - Rachel Douglas (Francosphères)
This article argues that books such as C.L.R. James’s The Black Jacobins (1938) and Aimé Césaire’s Cahier d’un retour au pays natal (1939) can be important postcolonial lieux de mémoire (sites or realms of memory). Examining where memory is crystallized in book form, the article explores the entangled genealogies and rewriting of both key Caribbean works. Both James’s history and Césaire’s poem were rewritten repeatedly over the decades. My argument is that these two Caribbean foundation stones are themselves key Caribbean sites of memory in their own right. Césaire’s Cahier becomes a crucial new element in James’s rewritten history. The article tracks the ongoing and layered process of memory as palimpsest through which James’s 1963 revised edition of The Black Jacobins is itself constituted. James’s creative translation and ‘misreading’ of Césaire’s poem is analysed as the means through which the Trinidadian Marxist makes the poem his own. This article explores a range of postcolonial memory sites including the 1968 Cultural Congress in Havana, Cuba, where both writers met, and the 1969 London performance of Cahier readings. Finally, the article considers the writers’ gravestones to see how the writers’ words have been used to memorialize James, Césaire, and their writing.